Beginning Microsoft Power BI : a practical guide to self-service data analytics - Clark, Dan (APress, 2020)
Analyze company data quickly and easily using Microsofts powerful data tools. Learn to build scalable and robust data models, clean and combine different data sources effectively, and create compelling and professional visuals. Beginning Power BI is a hands-on, activity-based guide that takes you through the process of analyzing your data using the tools that that encompass the core of Microsofts self-service BI offering. Starting with Power Query, you will learn how to get data from a variety of sources, and see just how easy it is to clean and shape the data prior to importing it into a data model. Using Power BI tabular and the Data Analysis Expressions (DAX), you will learn to create robust scalable data models which will serve as the foundation of your data analysis. From there you will enter the world of compelling interactive visualizations to analyze and gain insight into your data. You will wrap up your Power BI journey by learning how to package and share your reports and dashboards with your colleagues. Author Dan Clark takes you through each topic using step-by-step activities and plenty of screen shots to help familiarize you with the tools. This third edition covers the new and evolving features in the Power BI platform and new chapters on data flows and composite models. This book is your hands-on guide to quick, reliable, and valuable data insight. What You Will Learn: Simplify data discovery, association, and cleansing Build solid analytical data models Create robust interactive data presentations Combine analytical and geographic data in map-based visualizations Publish and share dashboards and reports Dan Clark is a senior business intelligence (BI) and programming consultant specializing in Microsoft technologies. He is focused on learning new BI and data technologies and training others on how to best implement the technology. Dan has published several books and numerous articles on .NET programming and BI development. He is a regular spea ker at various developer and database conferences and user group meetings and enjoys interacting with the Microsoft communities. In a previous life, Dan was a physics teacher. He is still inspired by the wonder and awe of studying the universe and figuring out why things behave the way they do.